Competitiveness of Slovenian Cargo Shipping - Počuča, Milojka (Promet - Traffic&Transportation)
The paper presents Slovenian cargo shipping, its system oforganisation, ownership, age and value stntcture. It shows theimportance of shipping in the Slovenian overseas trade and itsimpact on the state’s balance of payments. The analysis of thecompetitiveness of shipping was made from the viewpoint ofoperation costs and in comparison with the competitiveness ofEU shippers. The paper concludes with a proposal of possiblesystemic solutions which improve the competitiveness of Slovenianshipping.